2021
DOI: 10.1002/adma.202103755
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Robust Ionotronic Fiber with Unprecedented Mechanomodulation of Ionic Conduction

Abstract: unlike human tissues with rather complex and hierarchical structures, most of currently reported artificial ionic conductors, involving hydrogels, organohydrogels, ionogels, and ionic elastomers, were synthesized on the basis of a homogeneous solvent-swollen or salt-plasticized soft chain network. [4,[7][8][9][10][11] Despite high stretchability and optical transparency, such a soft network shows negligible or very small modulating effect on ion transportation; as a result, the ionic conductivity does not chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 56 publications
1
84
0
Order By: Relevance
“…[10][11][12] Moreover, the anisotropic mechanical properties of the LCEs can be harnessed to program their shape changes, enabling complex deformations including bending, coiling, twisting, and helixing. [3,13,14] Recently, significant progress has been achieved in the field of LCEs for materials synthesis, [15][16][17][18][19] fabrication, [16,[20][21][22][23][24] and expansion of LCE applications., [25][26][27][28][29][30][31] which has led to the renaissance of LCEs from both scientific and engineering aspects. However, the preparation of LCEs as actuators typically requires mesogen alignment prior to cross-linking, which leads to complicated fabrication processes unlike those required for fabricating conventional elastomers.…”
mentioning
confidence: 99%
“…[10][11][12] Moreover, the anisotropic mechanical properties of the LCEs can be harnessed to program their shape changes, enabling complex deformations including bending, coiling, twisting, and helixing. [3,13,14] Recently, significant progress has been achieved in the field of LCEs for materials synthesis, [15][16][17][18][19] fabrication, [16,[20][21][22][23][24] and expansion of LCE applications., [25][26][27][28][29][30][31] which has led to the renaissance of LCEs from both scientific and engineering aspects. However, the preparation of LCEs as actuators typically requires mesogen alignment prior to cross-linking, which leads to complicated fabrication processes unlike those required for fabricating conventional elastomers.…”
mentioning
confidence: 99%
“…; Δ R / R 0 = ε 2 + 2 ε ; Δ R is the resistance change (= R − R 0 ), R and R 0 the strain-dependent and initial resistances) at large strains. This is quite unusual, as most reported ionic conductors show only a moderate mechanoelectrical response (i.e., always lower than the conductivity-constant curve) 39 . The calculated gauge factor (GF = ∂(Δ R / R 0 )/∂ ε ) of hybrid ionic skin can reach as high as 66.8 at 630% strain, significantly higher than the ionic matrix (GF = 4.0) and conductivity-constant conductors (GF = 14.6) at the same strain (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…To clarify the mechanism of the substantially enhanced strain sensation of hybrid ionic skin, we first transformed the resistance changing curves in Fig. 4a to conductivity changes via the equation ( σ c / σ c,0 = λ 2 /( R / R 0 ); σ c and σ c,0 are the strain-dependent and initial conductivities, respectively) 39 , which reflect intrinsic structural changes without considering shape parameters. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al reported a robust iontronic fibre (IonoLCE) consisting of a rigid mesogen of RM257, a soft chain spacer of 2,2ethylenedioxy diethanethiol (EDDET), a crosslinker of pentaerythritol tetrakis (3-mercaptopropionate) (PETMP), and an ionic liquid of [BMIM + ][PF 6 À ]. 137 The diacrylate mesogens were reacted with the dithiol chain spacer and the tetrathiol crosslinkers via click Michael-addition reactions, in the presence of the IL (Fig. 13e).…”
Section: Aligned Iontronics Based On Liquid Crystal Elastomer (Lce)mentioning
confidence: 99%